Augmented reality media Assemblr Edu in Biology learning of the excretory system to increase student learning interest - Annisa Rezki Samosir; Kartika Manalu (Inovasi Kurikulum, 2025)
This study aims to develop and implement Augmented Reality (AR)-based learning media using the Assemblr Edu application in the context of Biology learning, especially on the excretory system material. The method used is Research and Development (RnD) with a 4D development model, which consists of four stages: Define, Design, Develop, and Disseminate. In the Define stage, needs analysis is conducted through interviews with teachers and questionnaires to students to identify challenges in learning. The Design stage includes making storyboards and developing interactive 3D organ excretory models. In the Develop stage, AR media is validated by material and media experts, and tested in class XI F1F, consisting of 36 students. The validation results show that the AR Assemblr Edu media achieved a score of 95.29 precent, which is considered "Very Valid". Teacher responses to the media reached 96.25 precent, and student responses showed a score of 95,63 precent, which is included in the "Very Practical" category. The student learning interest survey showed a score of 94.44 precent (4.78), which is included in the "Very High" category. These findings indicate that the AR Assemblr Edu media is not only effective in increasing students' interest and understanding of the excretory system but also provides an interactive and enjoyable learning experience. This study recommends the application of AR media in other Biology learning materials to increase student learning interest, especially in dealing with complex and abstract material.   Abstrak Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi media pembelajaran berbasis Augmented Reality (AR) menggunakan aplikasi Assemblr Edu dalam konteks pembelajaran Biologi, khususnya pada materi sistem ekskresi. Metode yang digunakan adalah Research and Development (RnD) dengan model pengembangan 4D, yang terdiri dari empat tahap: Define, Design, Develop, dan Disseminate. Pada tahap define, analisis kebutuhan dilakukan melalui wawancara dengan guru dan kuesioner kepada peserta didik untuk mengidentifikasi tantangan dalam pembelajaran. Tahap Design meliputi pembuatan storyboard dan pengembangan model 3D organ ekskresi yang interaktif. Pada tahap develop, media AR divalidasi oleh ahli materi dan media, serta diuji coba di kelas XI F1F yang terdiri dari 36 peserta didik. Hasil validasi menunjukkan bahwa media AR Assemblr Edu mencapai skor 95,29 persen, yang dikategorikan sebagai "Sangat Valid". Respons guru terhadap media mencapai 96,25 persen, dan respon peserta didik menunjukkan nilai 95,63 persen, yang termasuk dalam kategori "Sangat Praktis". Survei minat belajar peserta didik menunjukkan nilaim 94,44 persen (4,78) yang termasuk dalam kategori "Sangat Tinggi". Temuan ini mengindikasikan bahwa media AR Assemblr Edu tidak hanya efektif dalam meningkatkan minat dan pemahaman peserta didik terhadap materi sistem ekskresi, tetapi juga memberikan pengalaman belajar yang interaktif dan menyenangkan. Penelitian ini merekomendasikan penerapan media AR dalam pembelajaran materi Biologi yang lainnya untuk meningkatkan minat belajar peserta didik dalam pembelajaran, terutama dalam mengatasi materi yang bersifat kompleks dan abstrak. Kata kunci: Assemblr Edu; Augmented Reality; minat belajar; sistem ekskresi